GeoChip‐based analysis of functional microbial communities during the reoxidation of a bioreduced uranium‐contaminated aquifer - Joy D. Van Nostrand; Wei‐Min Wu; Liyou Wu; Ye Deng; Jack Carley; Sue Carroll; Zhili He; Baohua Gu; Jian Luo; Craig S. Criddle; David B. Watson; Philip M. Jardine; et al. (Environmental Microbiology, 2009)
Summary A pilot‐scale system was established for in situ biostimulation of U(VI) reduction by ethanol addition at the US Department of Energy's (DOE's) Field Research Center (Oak Ridge, TN). After achieving U(VI) reduction, stability of the bioreduced U(IV) was evaluated under conditions of (i) resting (no ethanol injection), (ii) reoxidation by introducing dissolved oxygen (DO), and (iii) reinjection of ethanol. GeoChip, a functional gene array with probes for N, S and C cycling, metal resistance and contaminant degradation genes, was used for monitoring groundwater microbial communities. High diversity of all major functional groups was observed during all experimental phases. The microbial community was extremely responsive to ethanol, showing a substantial change in community structure with increased gene number and diversity after ethanol injections resumed. While gene numbers showed considerable variations, the relative abundance (i.e. percentage of each gene category) of most gene groups changed little. During the reoxidation period, U(VI) increased, suggesting reoxidation of reduced U(IV). However, when introduction of DO was stopped, U(VI) reduction resumed and returned to pre‐reoxidation levels. These findings suggest that the community in this system can be stimulated and that the ability to reduce U(VI) can be maintained by the addition of electron donors. This biostimulation approach may potentially offer an effective means for the bioremediation of U(VI)‐contaminated sites.